Antimicrobial Regimens in Cement Spacers for Periprosthetic Joint Infections: A Critical Review - Symeon Naoum; Christos Koutserimpas; Ioannis Pantekidis; Vasileios Giovanoulis; Enejd Veizi; Maria Piagkou; Petros Ioannou; George Samonis; Aglaia Domouchtsidou; Andreas G. Tsantes; Dimitrios V. Papadopoulos (MDPI AG, 2024)
Antibiotic-loaded cement spacers (ALCSs) are essential for treating periprosthetic joint infections (PJIs) by providing mechanical support and local antibiotic delivery. The purpose of this review is to comprehensively examine the various types of spacers utilised in the management of periprosthetic joint infections (PJIs), including both static and articulating variants and to analyse the fundamental principles underlying spacer use, their clinical benefits, the selection and administration of antimicrobial agents, appropriate dosages, and potential adverse effects. Articulating spacers, which allow joint mobility, often yield better outcomes than static ones. Spacer pharmacokinetics are vital for maintaining therapeutic antibiotic levels, influenced by cement porosity, mixing techniques, and the contact area. Antibiotic choice depends on heat stability, solubility, and impact on cement's mechanical properties. Mechanical properties are crucial, as spacers must withstand physical stresses, with antibiotics potentially affecting these properties. Complications, such as tissue damage and systemic toxicity, are discussed, along with mitigation strategies. Future advancements include surface modifications and novel carriers to enhance biofilm management and infection control.